Zhonghua-Renmin-Gongheguo-fazhishi = The legal History of The People's Republic of China (Zhongguo-shehui-kexueyuan-wenku : Faxue-shehui-xue-yanjiu-xilie = The selected works of CASS : Law and sociology, 2010)
Abstract